Outpatient Waiting Time Acceleration: A Systematic Review of Process Improvement Interventions: Percepatan Waktu Tunggu Rawat Jalan: Tinjauan Sistematis Intervensi Peningkatan Proses - Yuniati, Rina; Fahrudda , Ansarul; Suswojo , Heru (Indonesian Journal of Innovation Studies, 2025)
Background (General): Prolonged outpatient waiting times remain a persistent challenge affecting patient satisfaction and healthcare service quality. Background (Specific): Although various process improvement strategies have been trialed, most focus solely on technical interventions, overlooking human and organizational factors. Knowledge Gap: There is limited comprehensive evidence synthesizing both technical and non-technical determinants of effective interventions for reducing outpatient waiting time. Aim: This study aims to systematically identify, evaluate, and classify the effectiveness of process improvement interventions in accelerating outpatient services, while also exploring supporting and inhibiting implementation factors. Results: Through a PRISMA-guided Systematic Literature Review (SLR), 17 studies were analyzed and categorized into five intervention groups: lean management, simulation-based algorithms, capacity-based scheduling and triage, IT automation, and hybrid approaches. Novelty: Unlike prior studies, this review integrates technical strategies with contextual human and cultural elements, offering a holistic framework for sustainable change. Implications: The findings emphasize that reducing outpatient waiting time requires not only technological upgrades but also organizational adaptation, leadership support, and patient education. This multidimensional understanding serves as a critical reference for policymakers and hospital administrators in designing more effective and enduring healthcare service improvements.Highlight : Interventions such as Lean, online appointment systems, and capacity-based triage effectively reduce outpatient waiting times. Technical approaches must be balanced with human factors and organizational culture for sustainable outcomes. Key barriers include resistance to change, limited budgets, and lack of integration between service units. Keywords : Waiting Time, Outpatient Services, Process Improvement, Hospital Information System, Lean Management